The changing character of fatal work injuries. - Toscano, Guy; Windau, Janice (Monthly Labor Review, 1994)
The 1993 Bureau of Labor Statistics Census of Fatal Occupational Injuries shows that the nature of deaths on the job is changing. In the U.S., about 5 out of every 100,000 workers in 1993 were fatally injured. Two-thirds of the deaths resulted from transportation-related incidents or from assaults and violent acts. Deadly contacts with heavy objects, machinery, and equipment—a traditional classification of work-related fatalities—accounted for about one-sixth of the total number of fatalities. Tables provide 1993 data on injuries, listed by type of event or exposure, by worker characteristics, by occupation, and by industry.